Adenosine Triphosphate in Serum as a Promising Biomarker for Differential Diagnosis of Hepatitis B Disease Progression - Lin, Caorui; Huang, Ying; Luo, Linjie; Fang, Fengling; Zhang, Jiawei; Xun, Zhen; Fu, Ya; Shang, Hongyan; Liu, Can; Ou, Qishui (Frontiers in Immunology, 2022)
The need to be diagnosed with liver biopsy makes the clinical progression of chronic HBV infection diagnosis a challenge. Existing HBV serum biochemical assays are used throughout clinical but have limited effects. Studies have shown that mitochondrial function is tightly coupled to HBV infection. Here, we verified the diagnostic value of serum Adenosine Triphosphate (ATP) as a potential marker for differential HBV infection progress by detecting the level of ATP in the serum from a wide spectrum of HBV-infected populations, and confirmed the role of ATP in the deterioration of HBV infection-related diseases through HBV-infected cells and mouse models. The results showed that there were significantly lower serum ATP levels in HBeAg-positive CHB patients compared with healthy controls. And during the progression of CHB to liver cirrhosis and hepatocellular carcinoma, the ATP level was increased but not higher than healthy controls. The area under the curve (AUC) of serum ATP was 0.9063 to distinguish HBeAg-positive CHB from healthy, and another AUC was 0.8328 in the CHB against the HCC group. Preliminary exploration of the mechanism indicated that the decline of serum ATP was due to impaired mitochondria in CHB patients. Our data provide evidence that serum ATP distinguishes the various progress of HBV infection-related diseases and expands diagnostic biomarkers for HBeAg-positive CHB patients with healthy controls.